AN ANALYSIS OF ENGLISH LEARNING STRATEGY APPLIED BY HIGH-ACHIEVING STUDENTS DURING STUDY FROM HOME - APRIANTI, ARIS DWI INTAN; GUNAWAN, GUNAWAN (GANEC SWARA, 2023)
This study aims to determine the English learning strategy used by high-achieving students of SMAN 1 and SMAN 2 Sumbawa during study from home (Belajar dari Rumah). This study involved 6 students as participants (3 students from SMAN 1 and 3 students from SMAN 2), all from 12th grade who have studied face-to-face and online. This is qualitative research, and the data were collected by using interviews and documentation. The results of this study show that the problems faced by the participants are the distribution of learning time, lack of interaction, difficulty in understanding the material and easily forgetting the material presented, limitations of media or learning facilities, network constraints, and a noisy house. The learning strategy used by the participants is a learning strategy. According to Oxford in 1990, there are 4 learning strategies from 6 learning strategies, namely memory strategy, cognitive strategy, compensation strategy, and social strategy. While the other two strategies they don't use are affective strategies and metacognitive strategies, The strategy that is high in use in several studies becomes low in use in this study, particularly due to the study from home period (SFH).